Catalogue of species of the subgenus Afromorgus Scholtz, 1986 (Coleoptera: Trogidae: Omorginae) known from the Oriental and Palaearctic Regions, including a description of one new species from the Deccan Plateau in India - Kalawate, Aparna S.; Strümpher, Werner P. (Zootaxa, 2024)
In this paper, we describe and illustrate another species of the family Trogidae, Omorgus (Afromorgus) moreshwar Kalawate & Strümpher, new species from the western part of Maharashtra State in India. In addition, a catalogue of all 22 valid species with their available synonyms of the subgenus Afromorgus Scholtz, 1986 known from the Oriental and Palaearctic Regions is presented. For each species we report type depository, type locality, chresonymy and distribution. Lectotypes are designated for the following species: Trox haagi Harold, 1872 (now Omorgus (A.) haagi), Trox indicus Harold, 1872 (now Omorgus (A.) indicus) and Trox lobicollis Arrow, 1927 (now Omorgus (A.) lobicollis). Omorgus (A.) desertorum (Harold, 1872), valid species, is redescribed and raised from a subspecies of Omorgus (A.) niloticus (Harold, 1872).